Biotin-decorated anti-cancer nucleotide theranostic conjugate of human serum albumin: Where the seed meets the soil?. Issue 3 (1st February 2018) - Popova, Tatyana V.; Khan, Hamda; Chubarov, Alexey S.; Lisitskiy, Vladimir A.; Antonova, Natalya M.; Akulov, Andrey E.; Shevelev, Oleg B.; Zavjalov, Evgenii L.; Silnikov, Vladimir N.; Ahmad, Saheem; Godovikova, Tatyana S.
Graphical abstract: Abstract: Human serum albumin is playing an increasing role as a drug carrier in clinical settings. Biotin molecules are often used as suitable tags in targeted anti-tumor drug delivery systems. We report on the synthesis and properties of a new multimodal theranostic conjugate based on an anti-cancer fluorinated nucleotide conjugated with a biotinylated dual-labeled albumin. Interestingly, in vitro and in vivo study revealed stronger anti-tumor activity of the non-tagged theranostic conjugate than that of the biotin-tagged conjugate, which can be explained by decreased binding of the biotin-tagged conjugate to cellular receptors. Our study sheds light on the importance of site-specific albumin modification for the design of albumin-based drugs with desirable pharmaceutical properties.